Electronic systems: mechanics' course in radio, television and electronics. - PATCHETT, G.N (Norman Price, 1969)
TABLA DE CONTENIDO: 1 Electrical safety: safe practices and avoidance of Danger. 2 Communication principles. 3 Methods of modulation and applications. 4 Characteristics of electronic unit